Discipline, Workload and Commitment Organizational on Performance Employees of PT Tirtakenca Tatawarna Makassar - Nursyamsi (IECON: International Economics and Business Conference, 2023)
This study aims to determine how much influence the quality of Discipline, Workload and Organizational Commitment on Employee Performance at PT Tirtakencana Tatawarna Makassar Branch. The analytical method used in this study is the method of observation, interviews, questionnaires, and documentation as well as the method of determining the sample using a total sample and obtained 6 0 respondents. The analysis method used is Multiple Linear Analysis. The independent variables Discipline, Workload and Organizational Commitment simultaneously affect employee performance, this is evidenced by the fcount value of 20,469 which is greater than the ftable of 2.77 and the significance value of 0.000 is less than 0.05, so it can be concluded that all the independent variables simultaneously and significantly influence the dependent variable. That is, there is an influence of Discipline, Workload and Organizational Commitment simultaneously on employee performance. The results of the determinant test show that the value of R2 is 0.5 94 which means that the amount of discipline, workload and organizational commitment to employee performance is 5 9.4% and the remaining 4 0.6 % is influenced by other variables